THE INFLUENCE OF DIGITAL FINANCIAL INCLUSION AND DIGITAL ACCOUNTING ON THE SUSTAINABILITY OF MSMEs IN KARAWANG REGENCY - Maula, Kholida Atiyatul (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
Implementation Inclusion Digital finance is necessary done as strategio For increase economy , in order to reduce level poverty , MSMEs have big role​ in development Indonesian economy however Still need done research advanced related implementation inclusion digital finance in MSMEs. Besides Many MSMEs in Indonesia do not yet understand or realize benefit digitalization as effort develop business . The reason is , digital technology is developing rapidly and had an impact on many matters , including MSMEs. Objective this research is test influence inclusion digital finance , digital accounting against sustainability of MSMEs in the district Karawang . With spread questionnaire to 100 MSME respondents in the district Karawang Research Results showing that Inclusion Digital Finance is influential to Sustainability of MSMEs while Digital Accounting does not influential to sustainability of MSMEs. Keyword: Inclusion Digital Finance , Digital Accounting, Business Sustainability , MSMEs